Aplicación de hallazgos provenientes de las ciencias sociales - Varela, Jacobo A. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
An example of the application of findings obtained from social science research for the solution of a problem is presented. Through the use of positive reinforcement, dissonance, reactance and other principles it was possible to modify in a short period of time the rough communication habits of a supervisor which made his interaction with his subordinates something less than successful.